DEEP SEISMIC IMAGES OF THE SOUTHERN ANDES - Yuan X.; Asch G.; Bock G.; Bohm M.; Echtler H.; Kind R.; Oncken O.; Ẅlbern I.; Bataille K. (My University, 2006)
Teleseismic earthquakes recorded within the ISSA (Integrated Seismological Experiment in the Southern Andes) temporary seismic experiment in the Southern Andes between 36° and 40°S latitude have been used to construct receiver function images of the crust and upper mantle. The oceanic Moho of the subducted Nazca plate is observed down to a depth of ̃100 km, corresponding well with the Wadati-Benioff zone seismicity and wide-angle seismic reflections. Beneath the volcanic arc, the slab begins to be invisible with P-to-S converted waves, implying the completion of the gabbro-eclogite transformation in the oceanic crust at that depth. The continental Moho has been imaged at depth of ̃40 km beneath the main cordillera and shallows toward the eastern end of the profile beneath the Neuquén Basin to ̃35 km depth. Beneath the Loncopué graben, the Moho is locally uplifted to 30 km depth, possibly resulting from the backarc spreading beginning in the Pliocene-Pleistocene. An anomalously high Poisson's ratio beneath the volcanic arc may indicate partial melting in the upper-plate crust. © 2006 Geological Society of America.
Keywords: MOHO; P-TO-S CONVERSION; RECEIVER FUNCTION; SLAB; SOUTHERN ANDES; SUBDUCTION ZONE; Pleistocene; Pliocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен